Cobaltand nickel-containing enzyme constructs from the sequences of methanogens - Chellapandi P.; Balachandramohan J. (Вiopolymers and Cell, 2012)
Aim. The conserved domain of sequences revealed in methanogens is considered for designing enzymes among which the attention has been focused on the metalloenzymes showing evolutionary significances. Methods. Molecular evolution, molecular modelling and molecular docking methods. Results. Molecular evolutionary hypothesis has been applied for designing cobalt-containing sirohydrocholine cobalt chelatase and nickel-containing coenzyme F420 non-reducing hydrogenase from conserved domains encompassing metaland substrate-binding sites. It was hypothesized that if any enzyme has similar or identical conserved domain in its catalytic region, the construct can bring similar catalytic activity. Using this approach, the region which covers such functional module has to be modeled for yielding enzyme constructs. The present approach has provided a high likelihood to design stable metalloenzyme constructs from the sequences of methanogens due to their low functional divergence. The resulted enzyme constructs have shown diverse reaction specificity and binding affinity with respective substrates. Conclusions. It seems to provide a new knowledge on understanding the catalytic competence as well as substrate-specificity of enzyme constructs. The resulted enzyme constructs could be experimentally reliable as the sequences originally driven from methanogenic archaea. Мета. Використати консервативний домен, отриманий із послідовностей метаногенів, для конструювання ферментів. Особливу увагу приділено металоферментам, оскільки вони мають важливе еволюційне значення. Методи. Теорія молекулярної еволюції, методи молекулярного моделювання і молекулярного докінгу. Результати. Конструювання кобальт-вмісної кобальтової хелатази і нікель-вмісного коферменту F420 нередукційної гідрогенази із консервативних доменів, оточуючих металі субстрат-зв’язувальні сайти, здійснено на основі теорії молекулярної еволюції. Зроблено припущення стосовно того, що якщо будь-який фермент містить у своєму каталітичному сайті схожий або ідентичний консервативний домен, то конструкції може бути притаманна подібна каталітична активність. Використовуючи цей підхід для створення ферментної конструкції, потрібно змоделювати ділянку, яка включає такий функціональний модуль. Даний метод забезпечує високу вірогідність одержання стабільних металоферментних конструкцій із послідовностей метаногенів через їхню низьку функціональну дивергенцію. Ферментні конструкції проявили різну реакційну специфічність і спорідненість при зв’язуванні з відповідними субстратами. Висновки. Очевидно, що будуть отримані нові знання для розуміння каталітичної спроможності, а також субстрат-специфічності ферментних конструкцій. Одержані ферментні конструкції можна застосовувати в експериментах як послідовності, що походять від метаногенної археї. Цель. Использовать консервативный домен, полученный из последовательностей метаногенов, для конструирования ферментов. Особое внимание уделено металлоферментам, поскольку они имеют важное эволюционное значение. Методы. Теория молекулярной эволюции, методы молекулярного моделирования и молекулярного докинга. Результаты. Конструирование кобальт-содержащей кобальтовой хелатазы и никель-содержащего кофермента F420 нередукционной гидрогеназы из консервативных доменов, окружающих металли субстрат-связывающие сайты, осуществлено на основе теории молекулярной эволюции. Сделано предположение о том, что если какой-либо фермент содержит в своем каталитическом сайте похожий или идентичный консервативный домен, то конструкция может обладать подобной каталитической активностью. Используя этот подход для создания ферментной конструкции, нужно моделировать участок, включающий такой функциональный модуль. Данный метод обеспечивает высокую вероятность получения стабильных металлоферментных конструкций из последовательностей метаногенов вследствие их низкой функциональной дивергенции. Ферментные конструкции проявляют различную реакционную специфичность и сродство при связывании с соответствующими субстратами. Выводы. Вероятно, будут получены новые знания для понимания каталитической способности, а также субстрат-специфичности ферментных конструкций. Полученные ферментные конструкции можно использовать в экспериментах как последовательности, происходящие от метаногенной археи.